2021
DOI: 10.1177/0960327121991899
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-26b-5p alleviates cerebral ischemia-reperfusion injury in rats via inhibiting the N-myc/PTEN axis by downregulating KLF10 expression

Abstract: MicroRNAs plays important role in cerebral ischemia-reperfusion (CIR). However, the role of miR-26b-5p in CIR injury remains unclear. PC12 cells were treated with oxygen-glucose deprivation (OGD) for 0 h, 2 h, 4 h, 6 h, and then reoxygenated for 24 h to construct an in vitro I/R model. Then, miR-26b-5p mimic, small interfering RNA of KLF10 and KLF10 overexpression plasmid were transfected into cells respectively for mechanism study. Our results showed that miR-26b-5p was downregulated in OGD/R-induced PC12 cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…To elucidate the mechanism by which KLF10 inhibits cell proliferation, we studied the PTEN/AKT pathway activation by KLF10 in AKI mouse models and renal tubular epithelial cells, because mounting evidence suggests that PTEN/AKT pathway has great negative effects on cellular proliferation and cerebral ischemia-reperfusion injury [ 28 , 34 , 35 ]. Decreasing PTEN with increasing phosphorylation of AKT was observed in IR-, cisplatin- and CLP-induced AKI mouse models (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To elucidate the mechanism by which KLF10 inhibits cell proliferation, we studied the PTEN/AKT pathway activation by KLF10 in AKI mouse models and renal tubular epithelial cells, because mounting evidence suggests that PTEN/AKT pathway has great negative effects on cellular proliferation and cerebral ischemia-reperfusion injury [ 28 , 34 , 35 ]. Decreasing PTEN with increasing phosphorylation of AKT was observed in IR-, cisplatin- and CLP-induced AKI mouse models (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To specify the exact mechanism, PTEN/AKT signaling was focused on for its roles of tumor suppressor and downstream of KLF10 in previous tumor study [ 28 , 34 , 35 ] and the same change of expression as KLF10 in AKI. At the same time, elevation of PTEN was examined in physical inhibition model and the late stage of tubular formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a bioinformatics analysis reported that miR-26b-5p can be recognized as a potential biomarker for IS (Barrera-Vázquez et al, 2022). Additionally, Xiao et al (2021) have observed that miR-26b-5p is downregulated in the brain of an MCAO rat model and that the overexpression of miR-26b-5p reduces apoptosis and the inflammatory response. Another study has shown that miR-26b-5p alleviates IS injury by negatively regulating the expression of Smad1, which promotes apoptosis and inflammation by increasing the level of ROS in cells (Shangguan et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…miR-26b-5p attenuated the TLR pathway by targeting CH25H and inhibited microglial M1 polarization, thereby attenuating CIRI nerve injury (94). In addition, MicroRNA-26b-5p attenuated cerebral ischemia-reperfusion injury in rats by down-regulating KLF10 expression and inhibiting the Nmyc/PTEN axis, reducing apoptosis and inflammatory responses (286). Further studies revealed that knockdown of the gene GAS5 could improve apoptosis and inflammatory responses by modulating the miR-26b-5p/Smad1 axis in CIRI rats.…”
Section: Mir-26b-5pmentioning
confidence: 99%